A hybrid improvement heuristic for the bin-packing problem and its application to the multiprocessor scheduling problem - Alvim, Adriana C. F.; Ribeiro, Celso C. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2004: Anais do XVII Concurso de Teses e Dissertações, 2004)
This work presents a hybrid improvement procedure for the bin packing problem and its application to the multiprocessor scheduling problem. This heuristic has several features: a new lower bound; reductions; initial solutions by reference to the dual problem; heuristics for load redistribution, and an improvement process utilizing tabu search. It improved the best known solutions for many of the benchmark instances and found the largest number of optimal solutions with respect to the other available approximate algorithms.